The role of yryms in the formation of the kazakh cultural code (Journal of Philosophy, Culture and Political Science, 2022)
As is well known, the customs and traditions of the Kazakhs are the unwritten law of the steppe; accordingly, superstition is one of the points of this great concept. The article discussed the life experience accumulated by the Kazakh people over the historical periods related to their natural and geographical environment. The article also provides an in-depth review of the views of domestic and foreign researchers on superstitions on child-rearing, on overcoming alien habits, and on preventing possible risks. As a nation that has undergone a certain historical development and cultural evolution, it has strengthened its emancipation. In order to protect them from the influence of giant world cultures, the Kazakh ornaments and ornaments have a special place in the formation of an original civilization. It is therefore important today to systematize the rituals that are the code of Kazakh culture. The article also looks at the role of the yryms in the modern context, i.e. adapting to modern Kazakh living conditions.Key words: Kazakh superstition, cultural code, spiritual consciousness, national symbol, continuity of traditions, system of national values